PENDIDIKAN BERBASIS BUDAYA (Presfektif Pemikiran H.A.R. Tilaar) - AGUNG KURNIAWAN DJIBRAN (JURNAL PENDIDIKAN GLASSER, 2017)
AbstractH.A.R. Tilaar emphasizes to the importance of education based on culture, because education is process of culture. Therefore, between the education and culture has been greatly relation, because the education is not able to be separated from culture that has reflected and grown up dynamically in Indonesian society.The purpose of this research is to determine how the education based on culture according to H.A.R. Tilaar’s perspective. The object of this research was H.A.R. Tilaar’s Perspective which concerns to the education based on culture.The approach of this research was literature review. The source of the data were a text book written by H.A.R. Tilaar and other literatures related to this research. The technique of analyzing data were the content analysis of the text book written by H.A.R. Tilaar and other literatures.The result of this research are : (a) H.A.R. Tilaar conceptualizes the education as an culturing processes; (b) the education process is an culturing process through the interactive process between teachers and students; (c) it is necessary to the Government of Indonesia to correct the National education concept by proposing several aspects such as ; (1) the basic value of education; (2) to notice the function of sociological education; (3) the relation between culture and education; (4) the education as The Agent ofChange, and (5) to get the equalization of education opportunity; and (d) to grow up the creative and adaptive thinking toward education phenomenawhich always move dynamically in the environment of the Indonesian community which has its complexity.Keyword: Education, Culture.